Aspectos da aplicação da geometria plana analítica como elemento de formalização na composição musical. - Rodrigues, Wander Vieira (2010)
This essay aims at describing a formalized compositional process that applies principles of analytical plain geometry in order to compose the symphonic music Euclidianas, which is a cycle consisting of three pieces: Transmutações I, II e III. Thus, this work is made up by three important points: The macro structural planning, the geometrical planning, and the musical composition. Besides the questions involving the process of textural connection and contrast approached by Mary Wennerstrom, the planning is emphasized by variation of the density parameter developed by Wallace Berry. These concepts were associated with the principles of analytical geometry, such as rotation, augmentation, diminution and deformation process in their individual or compound disposition to mold and develop the sound aggregates in the composition. The conception of this work based on the understanding of some aspects that are related to the formalized compositional process, which is very important to the learning and to the application of some available and developed tools in twentieth century music.